Strategy for Optimizing the Role of the Kapuas Hulu Police in Combating Drug Trafficking to Maintain Public Security and Order - Rinto Sihombing; Binsar Jon Vic S. (Indonesian Journal Publisher, 2026)
This study aims to analyze the legal regulations and strategies for optimizing the role of the Kapuas Hulu Resort Police (Polres) in combating drug trafficking in order to maintain public security and order. The problem of drug trafficking in Indonesia is a serious threat that impacts social stability and public security, thus requiring comprehensive countermeasures. This study uses a normative juridical legal research method with a statute approach and a conceptual approach. The legal materials used include laws and regulations, legal literature, and doctrines relevant to combating narcotics crimes and the role of the police in law enforcement. The results of the study indicate that regulations regarding narcotics countermeasures in Indonesia have been firmly regulated in Law Number 35 of 2009 concerning Narcotics and supported by the authority of the Republic of Indonesia National Police as stipulated in Law Number 2 of 2002 concerning the Republic of Indonesia National Police. In its implementation, the Kapuas Hulu Police have made various efforts to combat drug trafficking through repressive, preventive, and preemptive actions. However, various obstacles remain, including limited resources, extensive surveillance areas, and evolving modus operandi of drug trafficking networks. Therefore, optimization strategies are needed through increased human resource capacity, strengthened inter-agency coordination, the use of information technology, and increased public participation in drug prevention and eradication efforts to achieve a conducive public order and security.